Performance of Mango and Tamarind under Improved Microsite Condition in Degraded Drylands in Annur Block, Coimbatore District, Tamil Nadu - Madhu, M.; Sikka, A.K.; Singh, D.V.; Tripathi, K.P. (Journal of Soil and Water Conservation, 2022)
On farm field research studies were taken at Salaiyur watershed in Annur block of Coimbatore district under Integrated Wasteland Development Project during 1997 to study the performance of grafted mango and tamarind under degraded wastelands. The results of the study reveal that, pits filled with gravel free original soil and pond silt + FYM gave better survival per cent and gromh performance in terms of plant height and basal diameter. Grafts planted in mechanical pitting by JCB with microsite improvement through pits filled with sieved soil and/ pond silt + FYM gave better survival rate and growth performance due to improved water holding capacity and fertility status as compare to manual pitting at comparable cost.